Fixative Solution for Macromolecules in Histological Preparations - Hayu Swari Alimi; Ria Vena Septhay Sari; Tia Apriliyani; Ardaning Nuriliani; Bambang Retnoaji; Hendry Saragih; Zuliyati Rohmah (Berkala Ilmiah Biologi, 2023)
The fixation process is subjected to preserve cells, tissues, and their components so that the structure can be maintained as their alive condition and prevent autolysis. This literature review purpose to determine the appropriate use of fixative solutions for several macromolecules, such as proteins, lipids, carbohydrates, and nucleic acids. The literature review data is obtained form the secondary data included books, journals, or articles which discussed about fixative solutions without a limitation on the year of publication. The databases were sourced from Google Scholar, PubMed, NCBI, Science Direct, SpringerLink, Research Gate, and Nature. The keywords for the book search were tissue processing, pathology, and histology. Keywords for searching journals or articles were protein fixation, formaldehyde fixation lipids, fixatives for nucleic acids, Glyo-Fixx fixatives, mercury chloride fixative lipids, formalin-fixed carbohydrates, and ethanol or methanol for fixative lipids. Based on the literature review conducted, it can be concluded that the use of fixative solutions is according to the macromolecules to be observed.